2002
DOI: 10.1093/bioinformatics/18.10.1332
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian automatic relevance determination algorithms for classifying gene expression data

Abstract: We demonstrate the effectiveness of the algorithms on three gene expression datasets for cancer, showing they compare well with alternative kernel-based techniques. By automatically incorporating feature selection, accurate classifiers can be constructed utilizing very few features and with minimal hand-tuning. We argue that the feature selection is meaningful and some of the highlighted genes appear to be medically important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 14 publications
0
103
0
Order By: Relevance
“…Most recently, a Bayesian technique of automatic relevance determination, the use of support vector machines, and the use of ensembles of classifiers, all these either alone or in combination, have proved particularly promising. For further details see [Li et al (2002), Lu et al (2007), Chrysostomou et al (2008)] and the literature there. In the context of feature selection the last developments by the late Leo Breiman deserve special attention.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a Bayesian technique of automatic relevance determination, the use of support vector machines, and the use of ensembles of classifiers, all these either alone or in combination, have proved particularly promising. For further details see [Li et al (2002), Lu et al (2007), Chrysostomou et al (2008)] and the literature there. In the context of feature selection the last developments by the late Leo Breiman deserve special attention.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike correlation-based approaches, which consider the significance of individual features, the RVM considers the significance of a feature in the context of the features already selected, which may be useful in considering the effects of combinations of features on gene expression. This approach has been successfully used to find a small number of genes whose expression is diagnostic for certain cancer types (Li et al 2002). The discriminatory features selected by the RVM classifier included promoter motifs that had known functions in both glucose-and ABA-activated gene expression and revealed that light-responsive promoter motifs were powerful features for classifying promoters controlling glucose down-regulated gene expression.…”
mentioning
confidence: 99%
“…One of the issues we are addressing in this simplified context is the preprocessing (normalization) of gene expression data before the application of our classification procedures. Because of variabilities in gene expression measurements and uncertainties about the processing done by the tools used to generate the data, 7 we decided to include the effect of normalization as part of our studies. Specifically, for each data set we study, we attempt to learn via cross validation the most effective of a family of normalization parameters.…”
Section: Preprocessing the Data (Normalization)mentioning
confidence: 99%